A Bronze Age cairn and rapier find from Swaites Hill, Cloburn Quarry, South Lanarkshire. Issue 1 (March 2019) - Gordon, Douglas; McKinstry, Liam
Abstract : Rathmell Archaeology Ltd carried out the excavation of a disturbed kerbed cairn at Swaites Hill, Cloburn Quarry, South Lanarkshire. An inner and outer kerb were noted: the inner revealed two short cists, one containing two cremation burials. A third disturbed cremation burial with associated cordoned urn was present within cairn material between the inner and outer kerbs. A second urn and further cremated human bone deposits were found in the upper cairn material. The discovery of a Middle Bronze Age rapier within re-deposited cairn material hints at even more complexity; however, the full picture was sadly obscured by eighteenth to nineteenth century disturbance.